Armstrong Component Parts (Vietnam) Co., Ltd. In The Spoke Nipple And Rim Markets In Vietnam - Leong, Evans (2009)
The purpose of this thesis was to study on how can Armstrong Component Parts (Vietnam) Co., Ltd. maintain its market leadership in the Spoke and Nipple market and expand into the Rim market to enjoy greater market shareTujuan tesis ini adalah untuk mengkaji bagaimana Amstrong Component Parts (Vietnam) Co, Bhd boleh mengekalkan penguasaannya dalam pasaran "Spoke dan Nipple" dan memperluas dalam pasaran "Rim" untuk menikmati bahagian pasaran yang lebih besar.